Pengembangan LKPD pendidikan agama Islam dan budi pekerti berbasis inkuiri pada kelas VIII SMP Negeri 2 Bekri - Saputry, Nikky; Ehwanudin, Ehwanudin; Hayati , Rina Mida (Rafandha Press, 2024)
Background: Teaching in the 2013 curriculum emphasizes scientific methods, with one model that applies this approach being inquiry. Inquiry is considered a learning strategy that focuses on the role of students, where they are actively involved in a series of learning activities, including searching for information, analyzing and concluding the results of their findings during the learning process. Purpose: The aim of this research is to develop an inquiry-based Student Worksheet (LKPD) regarding belief in the books of Allah and love of the Koran and also determine the feasibility of the inquiry-based LKPD. Method: Employing the Research and Development (Rnd) methodology, the study follows Thiagarajan's 4D model: Define, Design, Develop, and Disseminate. Findings: LKPD is validated by material experts and media experts. Validation is carried out twice by the material validator. The final validation results by material experts reached a percentage of 96% in that